A Case of Overt GI Bleeding from a Obscured Source in a Cirrhotic Patient (Bangladesh Critical Care Journal, 2015)
While esophago-gastric varices are common manifestations of portal hypertension, variceal bleeding from the jejunum is a rare complication of liver cirrhosis. In addition, ectopic variceal bleeding occurs in the duodenum and at sites of previous bowel surgery in most cases, including of stomas. We report a case of obscure overt gastrointestinal bleeding from jejunal varices in a 70-year-old woman who had not previously undergone abdominal surgery, who had not diagnosed liver cirrhosis before. Emergency endoscopy revealed no esophageal varices but multiple nodular lesions with ulcerated tips with active oozing of blood and no bleeding focus was found at colonoscopy. She continued to produce recurrent melaena with hematochezia and received several units of packed red blood cells. CT angiography revealed the presence of jejunal varices, but no active bleeding was found. USG&CT scan of abdomen reveals coarse liver with splenomegally with mild pelvic collection. This is a case of variceal bleeding from the jejunum in a liver cirrhosis patient without a prior history of abdominal surgeryBangladesh Crit Care J September 2014; 2 (2): 81-84